2002
DOI: 10.1038/ncb786
|View full text |Cite
|
Sign up to set email alerts
|

A new nuclear component of the Wnt signalling pathway

Abstract: The Wnt signalling pathway is pivotal in normal and malignant development. A key effector is Armadillo (Arm)/beta-catenin, which functions with TCF to transcribe Wnt target-genes. Here, we report the discovery of pygopus (pygo), whose mutant phenotypes specifically mimic loss-of-Wingless (Wg) signalling. pygo is required for dTCF-mediated transcription, but not for Wg-induced stabilization of Arm. Pygo is a nuclear protein that is found in a complex with Arm in vivo. Humans possess two Pygo proteins, both of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
274
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(282 citation statements)
references
References 55 publications
7
274
0
1
Order By: Relevance
“…The higher levels of hPygo2 observed in HPV-infected cells and tissues suggested that it may, as in other cancers (2)(3)(4)(5)(6)39), have an important function in cervical cancer. HEN16T cells were therefore transfected with 2 siRNAs directed against hPygo2, siPy2-X, targeting its 3 0 -UTR and siPy2-Z targeting the coding region to determine the requirement of hPygo2.…”
Section: Hpygo2 Protein Is Overexpressed In Cin3 and Sccmentioning
confidence: 98%
“…The higher levels of hPygo2 observed in HPV-infected cells and tissues suggested that it may, as in other cancers (2)(3)(4)(5)(6)39), have an important function in cervical cancer. HEN16T cells were therefore transfected with 2 siRNAs directed against hPygo2, siPy2-X, targeting its 3 0 -UTR and siPy2-Z targeting the coding region to determine the requirement of hPygo2.…”
Section: Hpygo2 Protein Is Overexpressed In Cin3 and Sccmentioning
confidence: 98%
“…Further interactions between the β-catenin-TCF complex and chromatin could be mediated by Legless (Bcl9) and Pygopos [29][30][31]. Mutations in either of these genes result in wingless-like phenotypes in Drosophila, and both genes promote Wnt signaling in mammalian cell culture experiments [30].…”
Section: Signaling In the Nucleusmentioning
confidence: 99%
“…Mutations in either of these genes result in wingless-like phenotypes in Drosophila, and both genes promote Wnt signaling in mammalian cell culture experiments [30].…”
Section: Signaling In the Nucleusmentioning
confidence: 99%
“…It was identified through its association with BCL9/Legless, which binds to b-catenin ( Fig. 2A; Kramps et al 2002;Thompson et al 2002;Hoffmans and Basler 2004;Townsley et al 2004;Li et al 2007). That said, Pygo can also directly interact with TCFs in a Wnt-independent manner, where it appears to serve as a histone methylation reader and context-dependent LEF/ TCF anti-repressor to facilitate subsequent Wnt-dependent transcription (de la Roche and Bienz 2007;Mieszczanek et al 2008;Gu et al 2013).…”
Section: Overview Of Wnt Signaling Pathwaysmentioning
confidence: 99%